1982
DOI: 10.1055/s-2007-971259
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids fromFumaria parvifloraandF. kralikii*

Abstract: From Fumaria parviflora Lam. were isolated the major alkaloids protopine and adlumidiceine and the minor alkaloids parfumine, fumariline, dihydrofumariline, cryptopine, (-)-stylopine, 8-oxocoptisine, sanguinarine, and oxysanguinarine. The quaternary protoberberine fraction gave coptisine. Adlumidiceine, dihydrofumariline, 8-oxocoptisine, sanguinarine, and oxysanguinarine were found in F. parviflora for the first time. F. kralikii Jordan gave, besides the major alkaloids protopine, fumarophycine, and O-methylfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Phytochemical studies on Fumaria parviflora have shown the presence of alkaloids, such as, adlumidiceine, coptisine, fumariline, parfumine, protopine (Popova et al, 1982), fumaranine, fumaritine, paprafumicin, paprarine (Atta-ur-Rahman et al, 1992), fumarophycine, cryptopine, sanactine, stylopine, bicuculline, adlumine, perfumidine and dihydrosanguirine (Suau et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on Fumaria parviflora have shown the presence of alkaloids, such as, adlumidiceine, coptisine, fumariline, parfumine, protopine (Popova et al, 1982), fumaranine, fumaritine, paprafumicin, paprarine (Atta-ur-Rahman et al, 1992), fumarophycine, cryptopine, sanactine, stylopine, bicuculline, adlumine, perfumidine and dihydrosanguirine (Suau et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigation revealed the presence of several alkaloids such as adlumidiceine, copticine, fumariline, perfumine, protopine (Popova et al, 1982), fumaranine, fumaritine, paprafumicin and paprarine (Rahman et al, 1992). The plant has also been evaluated pharmacologically and shown to possess anthelmintic (Hordgen et al, 2003), antipyretic (Khattak et al, 1985), hepatoprotective (Gilani et al, 1996) and hypoglycemic (Akhtar et al, 1984) properties.…”
Section: Introductionmentioning
confidence: 99%
“…This medicinal plant contains several alkaloids and organic acids. Fumaric acid is one of its most efficacious components (25,26). Moreover, FP contains fumaric acid esters (FAEs) in addition to monomethylfumarate (MMF), the most bioactive metabolite of FAEs (24,27).…”
Section: Introductionmentioning
confidence: 99%